Artificial cryopreserved embryo transfer cycle success depends on blastocyst developmental rate and progesterone timing. Issue 3 (March 2018) - Ozgur, Kemal; Bulut, Hasan; Berkkanoglu, Murat; Humaidan, Peter; Coetzee, Kevin
Abstract: This retrospective cohort analysis compared the developmental competence of cryopreserved day-4 and 5 blastocysts, and investigated the effect of progesterone administration duration on the success of artificial frozen embryo transfers. Between October 2015 and March 2016, 868 intracytoplasmic sperm injection blastocyst cryo-all cycles were carried out, with 586 subsequently undergoing frozen embryo transfer. Of these, 243 were day-5 single blastocyst transfers (SBT) and 152 were day-4 SBT. Day-4 blastocysts were transferred on day-5 progesterone (day-4 group) and day-5 blastocysts were transferred on day-5 (short-protocol day-5 sub-group, n = 104) or day-6 (standard-protocol day-5 sub-group, n = 139) progesterone. Although more blastocysts were transferred in the standard-protocol day-5 sub-group ( P = 0.009), pregnancy, clinical pregnancy and live birth rates were similar to those of the day-4 group, but were significantly lower in the short-protocol day-5 sub-group ( P = 0.004, P = 0.008 and P = 0.02 respectively). For optimal outcomes, day-4 blastulating embryos should be prioritized for transfer on day 5 of progesterone and for day-5 blastocysts, transfer should be delayed by 1 day. The retrospective analysis and lack of adjustment for all known confounding variables limit the study.